OBSERVATION OF COASTAL FRONT AND CIRCULATION IN THE NORTHEASTERN JAVA SEA, INDONESIA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
The structure and spatial extent of a coastal front and circulation in the shallow (